Electrospun ultra-fine cellulose acetate fibrous mats containing tannic acid-Fe3+ complexes. (10th February 2017) - Yang, Weiqiao; Sousa, Ana M.M.; Fan, Xuetong; Jin, Tony; Li, Xihong; Tomasula, Peggy M.; Liu, LinShu
Highlights: Electrospun cellulose acetate (CA) fibers are loaded with tannic acid (TA)-Fe 3+ . The fibers show a tensile strength increase of 117% compared to that of neat CA. The antioxidant properties are comparable to those of mats loaded with TA alone. TA release is much slower in fibers loaded with TA-Fe 3+ complexes. Abstract: Cellulose acetate (CA) fibrous mats with improved mechanical and antioxidant properties were produced by a simple, scalable and cost-effective electrospinning method. Fibers loaded with small amounts of TA-Fe 3+ complexes showed an increase in tensile strength of ∼117% when compared to that of neat CA and were more resistant than those loaded with TA alone. The water uptake of the fibers increased upon TA or TA-Fe 3+ incorporation while their thermal behavior was only slightly affected. Fibrous mats loaded with TA-Fe 3+ showed comparable antioxidant activity with that of CA/TA mats, and a much slower TA release. These results suggest that TA-Fe 3+ complexes can be incorporated into electrospun CA fibers to improve their mechanical properties and antioxidant activity which may be of interest for the development of active packaging that can extend the shelf life of perishable foods.